Legacy effect of microplastics on plant–soil feedbacks - Lozano, Yudi M.; Rillig, Matthias C. (Frontiers in Plant Science, 2022)
Microplastics affect plants and soil biota and the processes they drive. However, the legacy effect of microplastics on plant–soil feedbacks is still unknown. To address this, we used soil conditioned from a previous experiment, where Daucus carota grew with 12 different microplastic types (conditioning phase). Here, we extracted soil inoculum from those 12 soils and grew during 4 weeks a native D. carota and a range-expanding plant species Calamagrostis epigejos in soils amended with this inoculum (feedback phase). At harvest, plant biomass and root morphological traits were measured. Films led to positive feedback on shoot mass (higher mass with inoculum from soil conditioned with microplastics than with inoculum from control soil). Films may decrease soil water content in the conditioning phase, potentially reducing the abundance of harmful soil biota, which, with films also promoting mutualist abundance, microbial activity and carbon mineralization, would positively affect plant growth in the feedback phase. Foams and fragments caused positive feedback on shoot mass likely via positive effects on soil aeration in the conditioning phase, which could have increased mutualistic biota and soil enzymatic activity, promoting plant growth. By contrast, fibers caused negative feedback on root mass as this microplastic may have increased soil water content in the conditioning phase, promoting the abundance of soil pathogens with negative consequences for root mass. Microplastics had a legacy effect on root traits: D. carota had thicker roots probably for promoting mycorrhizal associations, while C. epigejos had reduced root diameter probably for diminishing pathogenic infection. Microplastic legacy on soil can be positive or negative depending on the plant species identity and may affect plant biomass primarily via root traits. This legacy may contribute to the competitive success of range-expanding species via positive effects on root mass (foams) and on shoot mass (PET films). Overall, microplastics depending on their shape and polymer type, affect plant–soil feedbacks.